THE RELATIONSHIP OF MENTAL TOUGHNESS TO COMPETITIVE ANXIETY IN SMAN 4 WEST SUMATRA ATHLETES (SPORTS SPECIALIZATION) - Misel Yulia Ningsih, Misel Yulia Ningsih; Rinaldi (Causalita, 2024)
This study aims to see the relationship of mental toughness to competitive anxiety in West Sumatra SMAN 4 athletes. This study uses quantitative methods with correlational quantitative design. The population of this study were all athletes of SMAN 4 West Sumatra. The sampling technique used total sampling technique which amounted to 109 people. The instrument in this study used a mental toughness scale adapted from Clought (2002) and used a competitive anxiety scale adapted from Martens (1990). The results of the analysis using product moment analysis and the correlation coefficient (r) = 0.379 with a significant value of p = 000 (p <0.05) means that there is a significant positive relationship between mental toughness and competitive anxiety in West Sumatra SMAN 4 athletes. So it can be concluded that the higher the mental toughness, the lower the competitive anxiety in athletes.